Negative health outcomes in depressed cardiac patients are associated with both low and high psychological well-being dimensions. Issue 3 (16th March 2023) - Gostoli, Sara; Piolanti, Antonio; Buzzichelli, Sara; Benasi, Giada; Roncuzzi, Renzo; Abbate Daga, Giovanni; de Figueiredo, John M.; Rafanelli, Chiara
ABSTRACT: Literature supports the positive effects of psychological well-being (P.W.B.) on health. However, most studies focused on the unitary construct of P.W.B., neglecting the different role played by distinct P.W.B. dimensions on health-related outcomes. The aim of this study was to determine whether unbalanced (i.e. low or high) levels of P.W.B. dimensions could differentially affect cardiac course after acute coronary syndrome (A.C.S.), in terms of participation in secondary prevention (S.P.) and/or survival. The sample included 136 depressed and/or demoralized A.C.S. patients referred for a S.P. program on lifestyle modification, in addition to routine cardiac visits provided by the hospital where they were admitted. Psychological assessment included validated interviews on depression and demoralization, Symptom Questionnaire and Psychological Well-Being scales. 100 patients joined the S.P. program, 36 did not. Logistic regression revealed that older age (B = 0.051; p < 0.05), higher autonomy (B = 0.070; p < 0.05) and lower personal growth (B = −0.073; p < 0.05) levels were associated with non-participation in S.P. Moreover, only among patients who did not join the program, those presenting with an impaired level of P.W.B. 'positive relations' dimension (i.e. below the 25 th percentile) showed a worse cardiac prognosis (Log Rank: χ 2 (1)  = 4.654; p = 0.031). Negative health outcomes in depressed cardiac patients, such as non-participation in S.P. and worse cardiac course, are associated with both high and low levels of certain P.W.B. dimensions. Psychotherapeutic approaches geared to a balance in P.W.B. dimensions could represent promising new additions to S.P. programs.